Arendt's 'conscious pariah' and the ambiguous figure of the subaltern. (November 2016) - Ray, Larry; Diemling, Maria
Hannah Arendt's Jewish writings were central to her thinking about the human condition and engaged with the dialectics of modernity, universalism and identity. Her concept of the 'conscious pariah' attempted both to define a role for the public intellectual and understand the relationship between Jews and modernity. Controversially she accused Jewish victims of lack of resistance to the Nazis and argued that their victimization resulted from apolitical 'worldlessness'. We argue that although Arendt's analysis was original and challenging, her characterization of Jewish history as one of 'powerlessness' is exaggerated but, more importantly, her underdeveloped concept of 'the social' is insensitive to the complex modalities of resistance and consciousness among subaltern Jewish communities. Furthermore, her lack of interest in religious observance obscures the importance of Judaism as a resource for resistance. This is illustrated by the 'hidden transcripts' of Jewish resistance from the early modern period.